KRISIS NASIONAL: RESPONS PENDUDUK MISKIN DAN PEMERINTAH - Muhadjir Darwin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
The acute and complex national crisis persisting in this country has in general worsened the quality of live of the poor. However, empirical studies in five Javanese villages found that the impact of the crisis varies among different social groups, such as peasants, labors, small entrepreneurs and traders. This paper elaborates a number of factors that make the crisis affect differently to different people. This paper also shows how the poor develop their strategy of survival during the crisis and how government programs which attempt to eliminate the impacts of the crisis to the poor are in fact has failed to match the way the poor deal with the crisis.